Validation of a Cox prognostic model for tooth autotransplantation - Toshiya Yoshino; Michiko Yoshizawa; Shoko Aoyama; Toshiko Sugai‐Toyama; Kanae Niimi; Nobutaka Kitamura; Tadaharu Kobayashi (Wiley, 2023)
Abstract Objectives This study aimed to validate our Cox proportional hazards prognostic model for autotransplantation of teeth with complete root formation using prognostic index (PI) and determine whether the prognosis can be predicted. Patients and Methods The Protocol group, as a training data set for validation, consisted of 259 autotransplanted teeth to create a PI using the Cox model, as described previously. The Pre‐protocol group, as the first validation data set, consisted of 95 autotransplanted teeth treated without a protocol. The Post‐protocol group, as the second validation data set, consisted of 61 autotransplanted teeth obtained after the establishment of the prognostic model. Because four prognostic factors, including history of root canal treatment (yes), number of roots (multirooted), source of donor tooth (maxillary tooth), and duration of edentulism (≥2.5 months), were selected as a Cox prognostic model, 16 patterns of PI were constructed. First, the autotransplantated teeth in the Protocol group were divided into low‐ and high‐risk groups respectively according to the median of PI as the cutoff value. The survival curves of low‐ and high‐risk groups were calculated using the Kaplan-Meier method and tested using the log‐rank test. Then, in the Pre‐ and Post‐protocol groups, all transplanted teeth were divided into low‐and high‐risk teeth by the median of PI and the survival curves of low‐ and high‐ risk teeth were analyzed statistically in a similar manner. Results The survival curves of the low‐ and high‐risk groups diverged significantly in the Protocol and Post‐protocol groups. In the Pre‐protocol group, the curves of the low‐ and high‐risk groups were separated, and the low‐risk survival rate was improved. Conclusions Our Cox prognostic model for autotransplantation of teeth with complete root formation was useful in predicting the prognosis by external validation using PI.